2017
DOI: 10.2136/vzj2017.01.0033
|View full text |Cite
|
Sign up to set email alerts
|

Adsorbing vs. Nonadsorbing Tracers for Assessing Pesticide Transport in Arable Soils

Abstract: Core Ideas Atrazine preferential flow shortly after application was governed by soil type. Injection of atrazine at depth enhanced preferential flow. Uranine realistically illustrated the rapid and significant atrazine breakthrough. In reserve, bromide mimicked early atrazine breakthrough only with moraine soil. Using dye tracers as pesticide surrogates might assist in making sustainable decisions. The suitability of two different tracers to mimic the behavior of pesticides in agricultural soils and to evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
27
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 114 publications
(106 reference statements)
6
27
1
Order By: Relevance
“…Indeed, the pan samplers that are constructed in field settings can best represent the local field conditions and, although expensive, have great utility investigating groundwater pollution risks (Boesten, 2007; Köhne et al, 2009b), at least at the general soil class level. Our observation that pesticides are breaking through at the same time as the non‐adsorbed tracers has been noticed by others (Kladivko et al, 1991; Flury, 1996; Kung et al, 2000b; Torrentó et al, 2018). Thus, the similarity of travel time independent of the sorption properties is largely due to the fast flow of water and, consequently, the short time that is available for adsorption to occur.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Indeed, the pan samplers that are constructed in field settings can best represent the local field conditions and, although expensive, have great utility investigating groundwater pollution risks (Boesten, 2007; Köhne et al, 2009b), at least at the general soil class level. Our observation that pesticides are breaking through at the same time as the non‐adsorbed tracers has been noticed by others (Kladivko et al, 1991; Flury, 1996; Kung et al, 2000b; Torrentó et al, 2018). Thus, the similarity of travel time independent of the sorption properties is largely due to the fast flow of water and, consequently, the short time that is available for adsorption to occur.…”
Section: Discussionsupporting
confidence: 87%
“…Atrazine 2,4-D at least at the general soil class level. Our observation that pesticides are breaking through at the same time as the non-adsorbed tracers has been noticed by others (Kladivko et al, 1991;Flury, 1996;Kung et al, 2000b;Torrentó et al, 2018). Thus, the similarity of travel time independent of the sorption properties is largely due to the fast flow of water and, consequently, the short time that is available for adsorption to occur.…”
Section: Chloridesupporting
confidence: 82%
“…Finally, for the layered cartridges containing 8 g of SDB-1 and 8 g of Sepra ZT, matrix spikes were extracted to assess the influence of matrix components of real samples. To this end, known amounts of the target analytes (0.1 to 5 µg) were added to 10 L filtered (0.7-μm glass fibre filters) samples of agricultural drainage water 59 (Table 3). At 0.1 μg L -1 , similar recoveries were obtained for drainage water and tap water, except for DPC (24±30%) and DIA (35±14%).…”
Section: Resultsmentioning
confidence: 99%
“…Samples from the drainage water of lysimeters filled with arable soils were used. 59 Sorbent performance was evaluated in 10 L filtered (0.7-μm glass fibre filters) drainage water samples spiked with 0.1 to 50 µg L -1 of the target compounds. Finally, the integrity of the isotope values after large-volume SPE was assessed.…”
Section: Optimization Of the Large-volume Water Extraction Proceduresmentioning
confidence: 99%
“…For instance, Vallée et al (2015) found that the removal rates of boscalid in two pilot-scale wetlands ranged from 38 % to 67 %, whereas Gikas et al (2018) obtained removal rates for S-metolachlor (pesticide from the same group as metazachlor) that reached up to 92.6 % in a constructed wetland planted with Phragmites australis. Other authors have reported removal rates of between 45 % and 90 % for tebuconazole in wetland systems Tournebize et al, 2013). A possible explanation for the high removal rates obtained in our experiment could be the fact that contact of solutes with the medium was promoted due to a long period of stagnation (i.e., about 2 months in each run).…”
Section: Implications For Pesticide Mitigation In Wetland Systemsmentioning
confidence: 41%